Revisión bibliográfica sobre la enseñanza y aprendizaje del conflicto sociopolítico colombiano en la educación básica y media durante los años 2012-2020 - Martínez Lalinde, Fabio Leonardo (Universidad Antonio Nariño, 2022)
The object of study of this research consists of analyzing the state of the art of teaching and learning from educational pedagogical tools referring to the Colombian sociopolitical conflict at the elementary and high school level, during the peace agreement process 20122020. Thus, according to the prior criteria of the researcher it is intended to reflect on the main conceptualizations and methodological definitions related to the issue raised, in terms of improvements for teaching and education in a context of peace.